1980
DOI: 10.1063/1.440033
|View full text |Cite
|
Sign up to set email alerts
|

Chemiluminescence during the course of a reactive encounter; F+Na2→FNaNa‡*→NaF+Na*

Abstract: The intensity of the emitted visible radiation is studied for the temperature range 830–890 °K. (AIP)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…In addition, Kinsey and coworkers (78a,b) showed that, subsequent excitation, one could observe vibrationally resolved emission from the dissociating excited state, thereby learning how the geometry and vibrational modes of the molecule evolve as it dissociates. This experiment is essentially resonance Raman spectroscopy with a dissociative upper state; loosely speaking, it is a half-collision version of Polanyi's original state spectroscopy experiment (11). Kinsey's method unfortunately requires high concentrations of the species of interest and, so far, has not been used in experiments in which van der Waals molecules or negative ions are the transition state precursor.…”
Section: Photodissociation Of Stable Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Kinsey and coworkers (78a,b) showed that, subsequent excitation, one could observe vibrationally resolved emission from the dissociating excited state, thereby learning how the geometry and vibrational modes of the molecule evolve as it dissociates. This experiment is essentially resonance Raman spectroscopy with a dissociative upper state; loosely speaking, it is a half-collision version of Polanyi's original state spectroscopy experiment (11). Kinsey's method unfortunately requires high concentrations of the species of interest and, so far, has not been used in experiments in which van der Waals molecules or negative ions are the transition state precursor.…”
Section: Photodissociation Of Stable Moleculesmentioning
confidence: 99%
“…This has proved to be a considerable experimental challenge, because of difficulties involved in sl:udying the short-lived (10-12-10-15 s) complex formed in a reactive collision. Thus, for several years following the first experiments of this type of Polanyi and coworkers (11) and Brooks and coworkers (12) in 1980, there was at least as much discussion whether the results from transition state spectroscopy experiments were real as on what was being learned about reactive potential energy surfaces. However, during the last several years, a variety of frequency and timedomain experiments have been developed that have clearly yielded meaningful and detailed information on the transition state region.…”
Section: Introductionmentioning
confidence: 99%
“…Quantitatively, characterizing the fundamental basis of reaction pathway preference remains an elusive ideal to be reached in chemical reactivity, although recent advances in electron microscopy techniques have allowed direct observation of reactive intermediates despite their short lifetimes and high reactivities. 36,37 Thus, a better understanding of reaction mechanisms and product distributions can be achieved by molecular dynamics of reactions at or in the immediate vicinity of transition states, which can be complemented with experiments such as those performed by Polany 38 and Brooks, 39 the timeresolved pump-probe "femtochemistry" experiments pioneered by Zewail, 40 or the negative ion photodetachment experiments of Neumark 41 and Lineberger. 42 Thus, these experimental observations can be compared with predictions based on molecular simulations and/or transition state theory.…”
Section: Chemical Reactivity and Electron Densitymentioning
confidence: 99%
“…The following year he reported on his lab's early experimental TSS results-the visible chemiluminescence spectrum observed in the "wings" (570-630 nm) of the sodium D-line arising from the transition state, FNaNa ‡* (estimated to have a picosecond effective lifetime), for the reaction of F with Na 2 in a crossed-beam apparatus (20). Herschbach related his discussion (3) of reaction-product energy distributions in bimolecular reactions to the statistical treatment of the transition state in Rice-Ramsperger-Kassel-Marcus (RRKM) treatment of unimolecular rates.…”
Section: Interrelationshipsmentioning
confidence: 99%